An improved estrogenic activity reporter gene assay (T47D-KBluc) for detecting estrogenic activity in wastewater and drinking water. Issue 3 (4th March 2016) - Chou, Hui-Ming; Chao, How-Ran; Lin, Chieh; Chiang, Pen-Chi; Wang, Gen-Shuh; Tsou, Tsui-Chun
ABSTRACT: The estrogenic activity reporter gene assay (T47D-KBluc assay) is a useful method for detecting estrogenic activity in wastewater, but its resolving power and sensitivity are unsuitable in tap or drinking water. Our goal was to develop a new more sensitive method for detecting extremely low concentrations of estrogenic chemicals in drinking water. The sensitivity of estrogenic assay detection was improved in the present study by placing T47D-KBluc cells in phenol red-free medium for 12 h, and then exposing these cells to estrogenic compounds for a day prior to hormone analysis. A comparison of the new improved T47D-KBluc assay with the original conventional method showed that the new method markedly increased 17β-estradiol (E2 ) induced luciferase activation, sensitivity, precision, accuracy, and reproducibility but not limits of detection. Our results demonstrated that estrogenic activity was detectable in most samples of industrial effluents and five drinking water treatment plants utilizing the improved method. In conclusion, the sensitivity and resolving power of the improved method seems to be adequate for monitoring estrogenic activity in the inflow and outflow from drinking water and wastewater treatment plants.